2021
DOI: 10.1002/adom.202101909
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Triplet Excited States for Long‐Lived and Efficient Organic Afterglow

Abstract: In organic systems, it is very challenging to simultaneously achieve long afterglow lifetimes (τAG) and high afterglow efficiency (ΦAG). Here, luminescent dopants which feature a small rate of phosphorescence decay (kP) and modest rate of reverse intersystem crossing (kRISC) are designed and knr + kq values (nonradiative decay and quenching) of triplet excited states are suppressed by all means that include increasing molecular rigidity of luminescent dopants, screening organic matrices to strongly inhibit int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 94 publications
6
71
0
Order By: Relevance
“…The non-monotonic change of τ PF with matrix's dipole moments suggest that MeOBP matrices can simultaneously decrease k F and enhance k ISC of spiroBF 2 S 1 states via dipole-dipole interactions and significantly enhance intersystem crossing of spiroBF 2 excited states. [75] SpiroBF 2 -MeOBP materials have been found to exhibit afterglow The photophysical data of spiroBF 2matrix-1 % samples show that, with the increasing of matrices' dipole moments, the S 1 levels of spiroBF 2 decrease while T 1 levels of spiroBF 2 show less change, which caused the decrease of ΔE ST . b) Schematic illustration of the long-lived and efficient organic afterglow system characteristic of small k P , modest k RISC and very small k q + k nr , as well as the design strategies of the spiroBF 2 -MeOBP afterglow system.…”
Section: Enhancing Intersystem Crossing Via Dipole-dipole Interaction...mentioning
confidence: 97%
See 3 more Smart Citations
“…The non-monotonic change of τ PF with matrix's dipole moments suggest that MeOBP matrices can simultaneously decrease k F and enhance k ISC of spiroBF 2 S 1 states via dipole-dipole interactions and significantly enhance intersystem crossing of spiroBF 2 excited states. [75] SpiroBF 2 -MeOBP materials have been found to exhibit afterglow The photophysical data of spiroBF 2matrix-1 % samples show that, with the increasing of matrices' dipole moments, the S 1 levels of spiroBF 2 decrease while T 1 levels of spiroBF 2 show less change, which caused the decrease of ΔE ST . b) Schematic illustration of the long-lived and efficient organic afterglow system characteristic of small k P , modest k RISC and very small k q + k nr , as well as the design strategies of the spiroBF 2 -MeOBP afterglow system.…”
Section: Enhancing Intersystem Crossing Via Dipole-dipole Interaction...mentioning
confidence: 97%
“…A reduced ΔE ST can facilitate intersystem crossing of ICT dopants; this is the reason why dipole-dipole interactions in dopantmatrix systems can enhance intersystem crossing. [54,[73][74][75][76][77][78][79] Zhang reported that, by doping a BF 2 bdk compound, 530, into tetralone matrices at 1.0 wt%, the obtained 530-tetralone-1 % materials showed afterglow efficiency of 26 % and lifetime of 0.4 s under ambient conditions. [73] Similar to tetralone matrices, benzophenone and their derivatives also possess large dipole moments.…”
Section: Enhancing Intersystem Crossing Via Dipole-dipole Interaction...mentioning
confidence: 99%
See 2 more Smart Citations
“…S29, ESI†). The MeOBP matrices showed strong phosphorescence from 77 K to 240 K and thus largely interfered with the temperature-dependent phosphorescence measurements as reported in our recent study; 78 so benzophenone (BP) matrices were used in the place of MeOBP. At 77 K, the phosphorescence spectra of NPhRedBF 2 –benzophenone materials have been found to exhibit a structured emission band ranging from 630 nm to 850 nm with emission maxima at 658 nm (Fig.…”
Section: Resultsmentioning
confidence: 82%